Carbon nanotube reinforced alkali-activated slag mortars. (30th August 2016) - Rovnaník, Pavel; Šimonová, Hana; Topolář, Libor; Bayer, Patrik; Schmid, Pavel; Keršner, Zbyněk
Highlights: Application of MWCNTs in alkali-activated slag binders is introduced. Dosage of MWCNTs has a significant effect on the mechanical fracture properties of AAS composites. Acoustic emission method was used to monitor the hardening process of AAS mortars. Optimum dosage to obtain the best performance lies around 0.10% of MWCNTs. Abstract: The paper reports on a study of the effect of multi-walled carbon nanotubes (MWCNTs) when used as dispersed reinforcement on the fracture properties and microstructure of alkali-activated slag mortars. The amount of MWCNTs added varied in the range of 0.05–1.0% of the mass of slag. Mechanical and fracture properties were determined using fracture tests carried out on 40 × 40 × 160 mm specimens with a central notch. The observed parameters were compressive strength, modulus of elasticity, effective fracture toughness and specific fracture energy. Specimen response during fracture tests was also monitored by means of acoustic emission, and this method was also used for the determination of cracking tendency due to autogenous and drying shrinkage occurring during the hardening process. It is shown that the addition of up to 0.2% of MWCNTs improves the fracture properties of alkali-activated slag. Although a higher dosage of MWCNTs reduced the number of microcracks observed by acoustic emission, the mechanical properties of the slag deteriorated due to the less effective dispersion of the MWCNTs and the formation of bundles.